Early-Onset Neonatal Meningitis Caused by an Unusual Pathogen‐Moraxella catarrhalis. (9th January 2019) - Siwakoti, Shraddha; Bajracharya, Sohani; Adhikaree, Neetu; Sah, Rinku; Rajbhandari, Rupa Singh; Khanal, Basudha
Abstract : Introduction . Moraxella catarrhalis are part of the normal flora of the human respiratory tract and are known to have low pathogenic potential. The organism is rarely reported in the literature as the causative agent of meningitis. We report the first case of early-onset neonatal meningitis associated with M. catarrhalis from Nepal. Case Report . A 3-day-old baby with fever and yellowish discolouration of the body since 48 hrs was admitted to the neonatal ward. The baby developed 3 episodes of seizures in the form of uprolling of eyes on the first day of admission during phototherapy course for raised serum bilirubin. Sepsis screen was positive, and meningitis was confirmed as the cerebrospinal fluid culture grew M. catarrhalis. Cranial ultrasound scan was normal. The baby received a 21-day course of intravenous cefotaxime and amikacin. Recovery has been uneventful to date. Conclusion . Neonatal meningitis is a life-threatening infection. This case report presents an uncommon aetiology of neonatal meningitis which can be misidentified in the diagnostic bacteriology laboratory in resource constraints area like ours.